2020
DOI: 10.1038/s41598-020-73618-8
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of measles antibodies and factors associated with susceptibility: a national survey in Mexico using a plaque reduction neutralization test

Abstract: Measles continues to be one of the leading causes of child mortality worldwide, even though a highly effective vaccine has existed for more than 40 years. We aimed to describe the seroprevalence of measles antibodies in Mexico in 2012 and the risk factors associated with susceptibility. A total of 7,785 serum samples were analyzed from the National Health and Nutrition Survey in Mexico. This national survey is representative of the general population, including noninstitutionalized adult, adolescent, and child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Differences in seropositivity between males and females also support our hypothesis. In studies conducted in other countries, there was no difference in the measles seroprevalence according to sex [ 16 , 17 , 18 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, in our study, m-IgG seropositive rate in males was higher than that of females.…”
Section: Discussionmentioning
confidence: 89%
“…Differences in seropositivity between males and females also support our hypothesis. In studies conducted in other countries, there was no difference in the measles seroprevalence according to sex [ 16 , 17 , 18 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, in our study, m-IgG seropositive rate in males was higher than that of females.…”
Section: Discussionmentioning
confidence: 89%
“…The seroprevalence weighted proportion of our study was lower than that reported in the study by Diaz-Ortega et al , conducted in Mexico in 2012, who obtained a weighted prevalence of 99.37% (95% CI 99.07–99.58), using a plaque-reduction neutralization test. 32 They also found higher susceptibility in the group from 30 to 39 years of age. 32 …”
Section: Discussionmentioning
confidence: 90%
“…Diaz-Ortega et al , have observed as factors associated with susceptibility to measles at young ages, living in the country's capital, living in overcrowded conditions, and having an unknown vaccination stause or not having received a vaccine against measles between 1 and 5 years of age. 32 In Haiti, in 2017, Minta et al, observed higher susceptibility in regions where vaccine coverages were lower, using a multiplex bead assay to determine antibodies against measles. 37 …”
Section: Discussionmentioning
confidence: 99%
“…The group we were interested in this study were children aged between 1 and 4 years, of which 2.18% were susceptible to measles. The authors concluded that susceptibility was associated with young age, living in Mexico City, living in crowded households, and unknown or unvaccinated status among children ages 1–5 years, and drew attention to the importance of timely administration of the first dose of the vaccine at 12 months of age ( 37 ). Therefore, seroprevalence studies in the vaccinated population are important to assess the risks, show the real epidemiological conditions and indicate the reevaluation of the current immunization program in the country.…”
Section: Discussionmentioning
confidence: 99%